Tribological Behavior and Abrasion Resistance Mechanism of Laser Micro-Bulge Texturing Surface under Full Oil Lubrication. Issue 4 (3rd July 2020) - Hua, Xijun; Tian, Zhixiang; Xie, Xuan; Zhang, Peiyun; Xu, Jinfeng; Zhu, Yihang; Du, Hang; Yin, Bifeng
Abstract: This article aims to investigate tribological properties of a surface modified by laser texturing under full oil lubrication as well as the effect of laser texturing on the abrasion resistance properties. Laser texturing was carried out to fabricate a spherical bulge texture on the surface of GCr15 bearing steel using an SPI fiber laser. Rriction and wear tests were performed to simulate the actual situation of sliding friction under full oil lubrication. Mechanical properties of the micro bulge and substrate region were detected and analyzed using an optical microscope, microhardness tester, and residual stress detector. Friction and wear tests showed that under full oil lubrication, the friction coefficient (FC) of bulge-textured samples is positively correlated with texture density. Compared with a smooth sample, the FC of the sample with 50.2% texture density decreased by 64.4%. The sample with 28.2% texture density had a minimal wear volume (1.35 × 10 8 μm 3 ), which was diminished by 87.6% versus the smooth sample. The microstructure of the heat-affected zone is transformed into austenite by a large amount of heat and finally became acicular martensite when cooled. The microhardness of the bulge was increased to 419 and 331% of that of the substrate in vertical and radial directions, respectively. In addition, the surface of the micro bulge mainly revealed 20–35 MPa of residual tensile stress. The research proved that the surface wear resistance and antifriction effect of the sliding friction pair can be greatly improved by laser texturing, which shows favorable prospects for engineering applications such as bearings, guide rails, and mold formation.